PSI-26 Expression of cysteine/glutamate exchanger (SLC7A11) in different tissues including intestinal segments of broiler chickens. (7th December 2018) - Choi, J; Li, W; Schindell, B; Ni, L; Liu, S; Gong, J; Nyachoti, C; Yang, C
Abstract: Cysteine/glutamate exchanger (xCT, SLC7A11) is a component of the System Xc - amino-acid antiporter that can export glutamate and import cysteine into cells. The xCT amino acid exchanger has received a lot of attention because cysteine is an essential substrate for the synthesis of glutathione (GSH), an endogenous antioxidant in cells. The purpose of the research was to investigate the cloning and expression of xCT in different tissues, including intestinal segments of broiler chickens. A total of six 37-d old chickens were killed and the upper palate, tongue, heart, lung, liver, proventriculus, gizzard, kidney, duodenum, jejunum, ileum and colon were collected. The full-length coding region cDNA sequence of chicken xCT (2703 bp) was obtained from the jejunum by reverse transcription-polymerase chain reaction (RT-PCR) and then sequenced. The coding region cDNA sequence of chicken xCT has 80.4%, 80.2% and 71.2% homology with human, cattle and rat, respectively. Likewise, protein sequence analysis found that chicken xCT protein were 86.4%, 79.3% and 75.6% homologous with human, cattle and rat, respectively. Phylogenetic analysis indicated that chicken xCT were comparatively remote from cattle, human and rat. The chicken xCT has 12 transmembrane (TM) helixes, six extracellular loops and five intracellular loops. The mRNA of xCT were detected in all tissues including intestinal segments. In terms of intestinal segments, the mRNA expression of xCT was significantly higher ( P < 0.05) in the colon than mRNA expression of xCT in the jejunum and ileum. These results indicate that xCT is widely expressed both in intestinal segments which have a function of nutrient absorption and other organs that are not related to nutrient absorption such as proventriculus. Further investigation is needed to characterize the functional relevance of xCT activity in oxidative stress and inflammation in small intestine of broiler chickens.